2014
DOI: 10.1080/14767724.2014.934070
|View full text |Cite
|
Sign up to set email alerts
|

The making of the ‘precarious’: examining Indian immigrant IT workers in Canada and their transnational networks with body shops in India

Abstract: Since the 1990s, temporary staffing agencies have been playing a key role in managing and supplying a ready pool of skilled workers to the global IT market. Yet, such agencies often regulate their workforce to maintain flexible, low-cost and accommodating workers. Due to continuing racial and gendered barriers, many immigrant Indian IT professionals living in Canada are increasingly depending on many such India-based staffing agencies (body shops) to get into IT employment globally. Such associations I argue a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Branker (2017) and Pendakur (2005) noted negative labour market outcomes for Caribbean and Afghan immigrants in Canada. Maitra's previous paper (Maitra, 2015b) reported similar challenges faced by highly skilled South Asian immigrants in Canada. Despite being well qualified, many South Asian immigrants faced what can be described as the 'triple glass effect' while trying to translate their skills into appropriate opportunities in Canada.…”
Section: Transnational Migrants' Lifelong Learningmentioning
confidence: 78%
See 3 more Smart Citations
“…Branker (2017) and Pendakur (2005) noted negative labour market outcomes for Caribbean and Afghan immigrants in Canada. Maitra's previous paper (Maitra, 2015b) reported similar challenges faced by highly skilled South Asian immigrants in Canada. Despite being well qualified, many South Asian immigrants faced what can be described as the 'triple glass effect' while trying to translate their skills into appropriate opportunities in Canada.…”
Section: Transnational Migrants' Lifelong Learningmentioning
confidence: 78%
“…The government plans to boost the immigration programme further, to reflect 13% increase in immigration by 2020. Even though skilled immigrants bring significant human capital resources to Canada, a number of studies demonstrate that highly educated immigrant professionals experience deskilling and devaluation of their prior learning and work experiences after immigrating to Canada (Branker, 2017;Mojab, 1999;Guo, 2009Guo, , 2015aGuo, , 2015bMaitra, 2013Maitra, , 2015aMaitra, , 2015b. In a Vancouver based study with immigrants from the People's Republic of China, scholars found that most recent Chinese immigrants came to Canada with post-secondary education (72.5%).…”
Section: Transnational Migrants' Lifelong Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…Culture has thus been considered as unitary, static, and territorialized, "reproducing the image of the social world divided into bounded, culturally specific units, typical of nationalist thinking" (Wimmer & Schiller, 2002, p. 305). These forms of imagining national cultures as bounded categories have in turn reified certain dominant power relations and hierarchies of race or ethnicity as natural corollaries of national cultures rather than as historical effects of inequality and often violence (Maitra, 2015).…”
Section: Theorizing Transnationalism and Transculturalismmentioning
confidence: 99%